ANALISIS HUKUM NORMATIF TERHADAP PERSYARATAN KESELAMATAN DAN KEAMANAN DI WILAYAH PERAIRAN INDONESIA - Syukri, Muhammad (Universitas Prof. Dr. Hazairin, SH, 2022)
Abstract Indonesia is a maritime country surrounded by seas that are rich in natural resources, therefore a unified system is needed to maintain security and also to allocate all energy sources offered by the sea so that they can be managed properly. The management of waters safety and security in Indonesia is regulated in Law Number 17 of 2008 concerning Shipping. This article aims to review regulations regarding safety and security requirements in Indonesian waters and to analyze the authority of local governments in fostering shipping safety and security requirements in Indonesian waters. From a normative legal perspective, using a statutory and conceptual approach, it showed that the regulation of shipping guidance was carried out by the government. The form of guidance carried out by the government was in the form of supervision, control, and regulation. The legal protection of the implementation of regional autonomy was in line with the provisions of Law Number 23 of 2014 which involved local governments and carried out legal protection for various government affairs in the context of community service and natural resource management. Keyword : Safety ; Security ; Shipping Abstrak Negara Indonesia adalah negara maritim yang dikelilingi oleh laut yang kaya akan sumber daya alam, oleh karenanya dibutuhkan sistem kesatuan untuk menjaga keamanan dan juga untuk mengalokasikan segala sumber energi yang ditawarkan oleh laut agar dapat dikelola dengan tepat. Pengelolaan keselamatan serta keamanan perairan di Indonesia diatur dalam undang-undang Nomor 17 Tahun 2008 tentang Pelayaran. Artikel ini bertujuan untuk mengkaji peraturan mengenai persyaratan keselamatan serta keamanan di wilayah perairan Indonesia dan untuk menganalisis kewenangan pemerintah daerah dalam pembinaan terhadap persyaratan keselamatan dan keamanan pelayaran di wilayah perairan Indonesia. Dalam perspektif hukum normatif dengan menggunakan pendekatan peraturan perundang-undangan serta pendekatan konseptual, menunjukkan bahwa pengaturan pembinaan-pembinaan pelayaran dilaksanakan oleh pemerintah. Bentuk pembinaan yang dilakukan oleh pemerintah berupa pengawasan, pengendalian, serta pengaturan. Perlindungan hukum penyelenggaraan otonomi daerah sejalan dengan ketentuan Undang-Undang Nomor 23 Tahun 2014 yang melibatkan pemerintah daerah dan melaksanakan perlindungan hukum atas berbagai urusan pemerintahan dalam rangka pengabdian masyarakat serta pengelolaan sumber daya alam.